Description of a new Pterophoridae from Kazakhstan and new distribution records from central Palearctic region (Insecta: Lepidoptera) - K. Nupponen (SHILAP)
The Pterophoridae results of 60 expeditions to central Palearctic region during 1996-2019 are reported. Covered areas include the Volgo-Ural district, Southern Siberia, Central Asia, the Turanian region and the Caucasus. A new species is described from Kazakhstan: Procapperia processidactyla Nupponen, sp. n. from the Karatau Mountains. Agdistis flavissima Caradja, 1920 is reported as new to Europe from the lower Volga region. Previously unknown male genitalia of Agdistis karabachica Zagulajev, 1990 and Tabulaephorus maracandicus Arenberger, 1998 are illustrated. Distribution records of 42 species are reported.